2014
DOI: 10.1371/journal.pone.0108683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology of Rare Bleeding Disorders (RBDs) in India: A Systematic Review

Abstract: BackgroundThough rare in occurrence, patients with rare bleeding disorders (RBDs) are highly heterogeneous and may manifest with severe bleeding diathesis. Due to the high rate of consanguinity in many caste groups, these autosomal recessive bleeding disorders which are of rare occurrence in populations across the world, may not be as rare in India.ObjectivesTo comprehensively analyze the frequency and nature of mutations in Indian patients with RBDs.MethodsPubmed search was used (www.pubmed.com) to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…29,[63][64][65] This common mutation was also observed in India. 66 Arg326Gln FXIII-A gene mutation has been detected in patients from Germany and the Netherlands. 58,67 Thus, in patients with European origin, these three mutations can be selected as the first step in molecular diagnosis of FXIIID.…”
Section: Molecular Diagnosis Of Fxiiidmentioning
confidence: 99%
“…29,[63][64][65] This common mutation was also observed in India. 66 Arg326Gln FXIII-A gene mutation has been detected in patients from Germany and the Netherlands. 58,67 Thus, in patients with European origin, these three mutations can be selected as the first step in molecular diagnosis of FXIIID.…”
Section: Molecular Diagnosis Of Fxiiidmentioning
confidence: 99%
“…Our literature review identified a large number of novel mutations accounting for congenital fibrinogen disorders, both quantitative [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and qualitative. [65][66][67][68][69][70][71][72][73][74][75][76] The majority of dysfibrinogenemias, inherited as a dominant trait, are caused by heterozygous missense mutations in one of the three fibrinogen genes.…”
Section: Genetic Diagnosis Of Congenital Fibrinogen Disordersmentioning
confidence: 99%
“…Glanzmann's Thrombasthenia (GT) is a rare (1: 1 000 000) congenital bleeding disorder caused by dysfunctional or absent platelet integrin aIIbb3, because of mutations in the ITGA2B and ITGB3 genes located on chromosome 17q21-23 [1]. The clinical manifestations are highly heterogenous, which include mucocutaneous bleeding such as epistaxis, gum bleeding, haematuria, menorrhagia and gastrointestinal bleed resulting in major morbidity and mortality in affected families.…”
mentioning
confidence: 99%
“…The mutations which cause GT are spread all over the ITGA2B and ITGB3 genes. More than 200 mutations have been reported from across the world, which mainly comprise of deletions, point mutations, inversions, insertions and splice site variations, along with large number of polymorphisms [1]. The data published from Indian studies shows 47 unique mutations in 102 GT patients, while in 27 patients, mutation could not be detected despite scanning the entire coding, splice site and the regulatory regions of both the genes [1,3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation